Radiotherapy-specific interprofessional learning through simulation. Issue 1 (February 2021) - Ball, B.; Kirby, M.; Ketterer, S.-J.; Mullen, E.; Howard, L.; Bridge, P.
Abstract: Introduction: Interprofessional learning (IPL) is a vital aspect of training in radiation oncology professions, yet is rarely delivered to those professionals who work most closely together in clinical practice. Scenario-based learning using simulation facilities provides a unique opportunity to facilitate this learning and this project aimed to determine the impact and value of this initiative. Methods: Small groups comprising post-graduate diploma pre-registration therapeutic radiographers, medical physics trainees and radiation oncology registrars were challenged with 4 plausible and challenging radiotherapy scenarios within an academic simulation centre. Pre- and post-event completion of the "Readiness for Interprofessional Learning Scale" measured impact and a Likert-style survey gathered feedback from participants. Results: The session increased participants' teamwork and collaboration skills as well as strengthening professional identities. Participants reported high levels of enjoyment related to collaborative working, communication and observing other professionals deploying their technical skills and specialist knowledge. Conclusion: Although beneficial, simulated scenarios offering equal opportunities for engagement across the professions are challenging to plan and timetabling issues between the 3 groups present significant difficulties. The safe environment and unique opportunity for these groups to learn together was particularly well received and future oncology-specific simulated scenario sessions are planned with larger cohorts. Implications for practice: Simulated scenario training can be used to improve team working across the radiotherapy interprofessional team and may have wider use in other specialist interdisciplinary team development.